Serum Neurofilament Levels in Children With Febrile Seizures and in Controls - Evers, Katrina S.; Hügli, Melanie; Fouzas, Sotirios; Kasser, Severin; Pohl, Christian; Stoecklin, Benjamin; Bernasconi, Luca; Kuhle, Jens; Wellmann, Sven (Frontiers in Neuroscience, 2020)
Objective: Neuroaxonal damage is reflected by serum neurofilament light chain (sNfL) values in a variety of acute and degenerative diseases of the brain. The aim of this study was to investigate the impact of febrile and epileptic seizures on sNfL, serum copeptin and prolactin levels in children compared to children with febrile infections without convulsions. Methods: A prospective cross-sectional study was performed in children aging six months to five years presenting with fever (controls, n=61), febrile seizures (FS, n=78) or epileptic seizures (ES, n=16) at our emergency department. sNfL, copeptin and prolactin were measured within a few hours after the event in addition to standard clinical, neurophysiological, and laboratory assessment. All children were followed up for at least one year after presentation concerning recurrent seizures. Results: Serum copeptin values were on average 4.1-fold higher in FS and 3.2-fold higher in ES compared to controls (both p<0.01). Serum prolactin values were on average 1.3-fold higher in FS compared to controls (p<0.01) and without difference between ES and controls. There was no significant difference of mean sNfL values (95% CI) between all three groups, FS 21.7 pg/ml (19.6-23.9), ES 17.7 pg/ml (13.8-21.6) and controls 23.4 pg/ml (19.2-27.4). In multivariable analysis, age was the most important predictor of sNfL, followed by sex and CRP. Neither the duration of seizures nor the time elapsed from seizure onset to blood sampling had an impact on sNfL. None of the three biomarkers were related to recurrent seizures. Significance: sNfL is not elevated during short recovery time after febrile seizures when compared with children presenting febrile infections without seizures. We demonstrate an age-dependent decrease of sNfL from early childhood until school age. In contrast to sNfL levels copeptin and prolactin serum levels are elevated after febrile seizures.